قراءة في قوانين التعويض عن الكوارث في التشريع المغربي - ضالع، ليلى (محمد قاسمي, 2023)
يعنى هذا البحث بقراءة لقوانين التعويض عن الكوارث في التشريع المغربي، بين القواعد الخاصة بأحكام التعويض الفوري عن الكوارث من خلال الاستفادة من صندوق التضامن، والقواعد العامة المتعلقة بالتعويض على أساس المسؤولية العادية. This research is concerned about the disaster compensation laws in Moroccan legislation, and he explained the rules for immediate compensation for disasters by the Solidarity Fund, and the rules for compensation on the basis of regular liability related.
Keywords: الكوارث الطبيعية -- التعويض عن الكوارث -- مسؤولية الدولة -- القانون المغربي